pH-imprinted lipase catalyzed synthesis of dextran fatty acid ester - Kulthida Kaewprapan (2018)
The application of enzymatic catalysis for the synthesis of polysaccharide-based surfactants was investigated. The polysaccharide dextran, a neutral bacterial polysaccharide consisting of α-1,6 linked glucose units, was chemically modified by the attachment of hydrophobic groups through a transesterification reaction with a vinyl decanoate. A screening of commercially available lipases and protease for the synthesis of amphiphilic polysaccharides in DMSO suggested that lipase AY from Candida rugosa modified dextran T-40 with vinyl decanoate at the highest conversion. A pH-adjustment in a phosphate buffer at pH 7.5 prior to use is crucial to make this enzyme active in DMSO. The effect of enzyme concentration and mole ratio of fatty ester to dextran T-40 on the conversion and the rate of reaction were studied. Finally, investigation of the kinetics and regioselectivity of lipase AY-catalyzed modification offer a possibility to regulate the position and the extent of hydrophobic group attached to dextran. These two properties are fundamental for controlling the physico-chemical properties of the final polymeric surfactants. © 2007 Elsevier B.V. All rights reserved.